2009
DOI: 10.1097/icu.0b013e32832ec3e0
|View full text |Cite
|
Sign up to set email alerts
|

Management of canalicular obstructions

Abstract: The alternative techniques to conjuctivodacryocystorhinostomy are less invasive, and respect and utilize any healthy and functional part of the canalicular system. The correct choice of the technique for a given canalicular obstruction, and therefore the long-term success, depends on the site and degree of the obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…Other approaches for canalicular obstruction such as canalicular trephine and laser are associated with few complications and are well tolerated. However, they have a lower rate of success 1 3 9 10…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other approaches for canalicular obstruction such as canalicular trephine and laser are associated with few complications and are well tolerated. However, they have a lower rate of success 1 3 9 10…”
Section: Discussionmentioning
confidence: 99%
“…The overall satisfaction rate was 93.3%. Success rate of laser canaliculoplasty and trephination varies (43–87% symptomatic success at 12 months) 1 3 8. RC-BCI treatment achieved a relatively high success rate compared with laser canaliculoplasty and trephination for canalicular obstructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In congenital anophthalmos or severe microphthalmos the lacrimal system is affected in up to 78% of the cases, mostly due to canalicular stenosis (58%), and less commonly, common canalicular stenosis (7.3%) 6263…”
Section: Canalicular Stenosismentioning
confidence: 99%
“…Currently, surgery is the major mode of therapy for treating lacrimal passage obstruction; however, the success rate of this intervention remains unsatisfactory [6]. It has been previously reported that for complex congenital NLDO in infants older than 1 year of age, the success rate of probing lacrimal passage within 6 months is only 47.4% [7].…”
Section: Introductionmentioning
confidence: 99%